Relationship Between Technology Leadership, ICT Facility, Competency, Commitments Towards Effectiveness of School Mangement Tasks in Schools: Hubungan Antara Kepemimpinan Teknologi, Fasilitas TIK, Kompetensi, Komitmen Terhadap Efektivitas Tugas Manajemen Sekolah di Sekolah - Raman, Arumugam; Shariff, Som binti (Universitas Muhammadiyah Sidoarjo, 2018)
Previous studies more engaged to the level of technology leadership and the characteristics of technological leadership practiced by leaders in the school, while the factors of a more comprehensive which include facilities for ICT, competence, and commitment of teachers in the practices of applying ICT in the management which contributes a great impact on the management duties of teachers in schools has not been studied in Malaysia. The purpose of this study is to identify whether there is a positive relationship between technology leadership, ICT facilities, competence, commitment and practice of applying ICT teachers with effective management duties of teachers in schools using ICT. This quantitative study involves 370 teachers in secondary schools in the Kedah state which were selected randomly. The findings from the analysis of the study using the smartPLS show that there is a significant relationship between the leadership of technology by principals in school and the effectiveness of teacher-management tasks using computers in management tasks. Leadership that practices high technology leadership features will have a positive impact on the effectiveness of ICT integration within the organization. Further study can be conducted with integrating UTAUT model to identify critical factors that contributing technology leadership in schools.